(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines effective methods for developing the physical abilities of school-age students through gymnastics within the framework of the New Uzbekistan Development Strategy. The study substantiates the pedagogical significance of gymnastics as a universal means of improving strength, flexibility, agility, coordination, speed, and endurance in the school education system. Special attention is paid to the fact that gymnastics not only strengthens students’ physical preparedness but also contributes to the formation of discipline, willpower, self-confidence, attentiveness, and a stable motivation for regular physical activity. The article analyzes contemporary methodological approaches aimed at improving physical education lessons, including differentiated instruction, age-appropriate exercise selection, gradual increase of physical load, game-based tasks, and health-preserving technologies. It is emphasized that gymnastics serves as an effective educational tool for ensuring the harmonious development of learners, strengthening health, preventing hypodynamia, and increasing interest in physical culture. The article also considers the organizational and methodological conditions required for the effective use of gymnastics in schools, including teacher competence, lesson planning, safety standards, and the integration of national development priorities into educational practice. Based on theoretical analysis and pedagogical interpretation, the study concludes that gymnastics plays an important role in raising a physically active, healthy, and socially responsible younger generation.